Perkembangan Ekonomi Berbasis Digital Di Indonesia - Sindy Lita Kumala (Journal of Economics and Regional Science, 2022)
The purpose of this study is to determine the development of a digital-based economy in Indonesia. The method used in this research is descriptive. The digital economy was born and developed along with the use of Information and Communication Technology which is also increasingly globalized in the world. The digital economy has a significant impact on the Indonesian economy. Data from the Central Statistics Agency (BPS) shows that in 2017 the contribution of the digital market to Indonesia's Gross Domestic Product (GDP) increased by 4 percent compared to 2016 of 3.61 percent, and in 2018 it is estimated to reach 10 percent. Technological developments have brought rapid changes and intense competition. Human mobility, the distribution of goods, as well as the traffic of capital and information are rapidly developing through digitization. The development of digitalization has created new breakthroughs in the financial sector, the cultural sector, tourism and the creative economy, the agricultural sector and the agrologistics sector